Music as territory: Aksim Siming and stringband music in the Madang area - Suwa, Junichiro (Perfect Beat, 2009)
This paper discusses sociocultural changes in music in post war Papua New Guinea, by presenting examples of under-researched early stringband activities in the Madang area. The musicians as social actors are seen to be undertaking an act of what the author calls ‘territorialization’, a means of cultural survival through music-making in an era of transition from traditional local chiefdom to modern independent state. The case of Aksim Siming of Kranket, a key figure in the early phases of Madang stringband music, will be presented, along with details of others who participated in guitar and bambooband activities.